(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Understanding how river flow regimes may evolve under changing climatic conditions is fundamental for sustainable water resources planning, particularly in tropical monsoon river basins where streamflow exhibits strong seasonal variability. This study presents a novel framework for assessing future hydrological flow regimes at a 10-daily timescale under near-future climate scenarios and subsequently examines the associated seasonal variability in streamflow and baseflow components. The framework was implemented in the Brahmani River Basin (39,116 km²) located in eastern India, a region characterized by pronounced monsoonal hydrology. The semi-distributed Soil Water Assessment Tool (SWAT) model was employed to simulate historical streamflow dynamics and demonstrated satisfactory performance in reproducing observed hydrological behaviour. Future climate projections for the basin were obtained from the REMO regional climate model under three Representative Concentration Pathways (RCP2.6, RCP4.5, and RCP8.5). Changes in future flow regimes were analysed using flow duration curves (FDCs) developed at a 10-daily timescale, while long-term trends in streamflow and baseflow were evaluated using the non-parametric Mann-Kendall test and Theil-Sen slope estimator. Baseflow separation was performed using the Recursive Digital Filter (RDF) method based on hydrograph recession characteristics. The results reveal a tendency towards increasing streamflow and baseflow during the near-future period (2021-2045), suggesting enhanced water availability in the basin under projected climatic conditions. By capturing hydrological variability at a finer temporal resolution, the proposed framework provides improved insights into future water availability and seasonal flow characteristics. The methodology is readily transferable to other river basins and offers a practical basis for climate-resilient water resources planning and management in monsoon-dominated regions.